THE IDENTIFIKASI KEBUTUHAN MEDIA DALAM TERAPI WICARA: LANGKAH MENUJU METODE YANG EFEKTIF: IDENTIFICATION OF MEDIA NEEDS IN SPEECH THERAPY: STEPS TOWARDS AN EFFECTIVE METHOD - Ekasari, Tetty (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
This study aims to identify the therapy media used by speech therapists in carrying out therapy on patients/clients with language and/or speech disorders, both children and adults. Language and/or speech disorders, both children and adults, are cases of disorders that are often handled by therapists in the city of Bandung based on a questionnaire survey. The method in this study is descriptive qualitative research. The subjects were 40 therapists in Bandung. The object of this study is the media needs and therapy methods used by therapists in handling clients with language and speech disorders. The data collection technique was the distribution of questionnaires to 40 therapists. The results showed that the therapy media widely used by therapists were picture/word cards (flash cards). While the method widely used in patients/clients with language and/or speech disorders was Multimodal Stimulation.